CERDAS MENGELOLA KEUANGAN RUMAH TANGGA, STRATEGI INVESTASI AMAN BAGI MASYARAKAT KOTA TEBING TINGGI - Sinurat, Mangasi; Siahaan, Rumiris; Purba, Rakhmawati; Hartanto, Bobby; Arneta, Yaumi Arfah Noor; Lumban Tobing, Maria Magdalena; Lubis, Mhd Ridho Akbar; Andika, Andika; Victor, Victor; Cittaro, Michael; Nasution, Umar Hamdan; Nasution, Roni; et al. (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2025)
Household financial management is crucial for a family's operational well-being. Managing finances requires precision and ingenuity. This must be adjusted to the family's income, which will be used for daily expenses and a portion set aside for savings and investment. The problem arises from a lack of financial literacy, resulting in many housewives lacking an adequate understanding of basic financial concepts, such as budgeting, distinguishing between needs and wants, and even not knowing how to save and invest their money. The implementation of the Ceria Village Community Service Program (KKN) involving students, lecturers, and partners. Conducting outreach to the community and providing financial literacy in the villages of Bagelen, Pelita, and Pinang Mancung. The objective of this activity was to strengthen understanding of financial literacy and investment, with the theme "Smart Household Economy, Safe Investment." The outreach method used included lectures and a Q&A session. Discussions, including the material and Q&A sessions, addressed issues emerging during the event, and quizzes were administered to improve participant understanding. The results showed that participants gained new knowledge about family financial management and recognized the importance of financial literacy in improving family well-being.